2010
DOI: 10.2474/trol.5.165
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Adsorption Structures of Friction Modifiers by Means of Quantitative Structure-Property Relationship Method and Sum Frequency Generation Spectroscopy

Abstract: Blending an optimum amount of friction modifiers into lubricant is one of the important measures to reduce fuel consumption induced by the frictional loss for automobiles. However, the agents containing metal or phosphorus compounds can cause catalyst poisoning and clogging in the filters of the exhaust gas refining system. Thus, development of metal-free and phosphorus-free agents with a long-term stability under real working condition is highly desirable. In the present work, the friction coefficients on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…These include the surface forces apparatus (SFA) [58][59][60][61], atomic/lateral force microscope (AFM/LFM) [62][63][64][65], quartz crystal microbalance (QCM) [66], ultrathin film interferometry (UTFI) [67], neutron reflectometry [68,69] and various surface-specific vibrational spectroscopies [70][71][72]. Methods were also developed to generate model close-packed monolayers by chemical grafting of self-assembled alkylthiols and alkyl siloxanes on solid surfaces [73][74].…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the surface forces apparatus (SFA) [58][59][60][61], atomic/lateral force microscope (AFM/LFM) [62][63][64][65], quartz crystal microbalance (QCM) [66], ultrathin film interferometry (UTFI) [67], neutron reflectometry [68,69] and various surface-specific vibrational spectroscopies [70][71][72]. Methods were also developed to generate model close-packed monolayers by chemical grafting of self-assembled alkylthiols and alkyl siloxanes on solid surfaces [73][74].…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…Beattie and co-workers studied a Langmuir-Blodgett film of zinc arachidate in sliding sapphire/quartz contacts and found that film order was maintained during sliding but some film was transferred from the monolayer to the opposing surface [87]. In a recent study by Koshima et al the friction coefficients of solutions of a range of model OFMs were correlated with the SFG spectral characteristics of their selfassembled films on iron, suggesting that OFMs that give the most ordered surface films also show the lowest friction [72].…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…They are widely used as additives in low friction lubricant formulations, including modern, fuel-efficient engine oils. Typical OFM structures are shown in [1]. Although OFMs have been in use for almost a century [2], there is still considerable debate about the nature of the boundary films that they form.…”
Section: Introductionmentioning
confidence: 99%
“…In the present Personal Account, our recent SFG studies on the molecular structures at interfaces of functional soft matter such as polymers, self‐assembled monolayers (SAMs) and Langmuir–Blodgett (LB) ultrathin layers and lipid bilayers in various environments will be briefly reviewed. A general model dealing with the optical interference effect in thin layers of soft matter, which can dramatically affect the SFG spectral shape and intensity, will be introduced first.…”
Section: Introductionmentioning
confidence: 99%